Modifikasi Pengering Tenaga Surya dengan Ventilator Otomatis - Subarjo Subarjo; Tri Widodo; Muhammad Yusfiar Karfiandi (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
Radiant energy from the sun is one of the alternative energy sources to replace the role of oil as a primary energy source. Alternative forms of energy that can be used is to dry the material/material. One form of utilization of solar radiation energy is raising the air temperature. Solar collector is one example of the utilization of solar energy. Moving the hot air from the collector to the drying chamber is accelerated by a ventilator installed above ruangpengering. Dryer tool consists of two parts, solar collector and drying chamber that can directly receive the energy from the sun. Measurements were performed in this study is the temperature (T), humidity (Rh) and air velocity (v) who are outside and inside the drying chamber. Measurements were taken during the 5 days of observation starts at 11:00 until 15:00. an interval of one hour of measurement. The drying chamber reaches the maximum temperature at 11:00 until 13:00 with a temperature of 40.6â°C while outside the drying chamber (conventional) only 39.8â°C occurred at 12:00 hours until 13:00. kelemban (Rh) diruang dryers lower than outside the room pengring an average of 47.44% and 57.24% outside the drying chamber, the air flow in the drying chamber of 0.695 m/sec is still higher when compared with data obtained on the appliance dryer without a ventilator that is 0.195 m/sec. obtained water content (KA) end at 18.67% drying within 5 days, whereas for conventional drying KA obtained by 27.11%.Â Keywords: collector, ventilator, drying